The Effect of Blood Pressure On The Quality of Daily Sleep In The Elderly In PSTW Pandaan - Hannan, Mujib; Hidayat, Syaifurrahman; Fatoni, Akhmad Feri (STRADA : Jurnal Ilmiah Kesehatan, 2021)
The blood pressure normally increases in the elderly, making them subject to greater risk of hypertension. This is compounded by poor quality of sleep which leads to a further increase in the blood pressure. The method was analytic correlation using cross sectional design. The population included adults above 45 years old in Tresna Wedha Nursing Home (PSTW) in Pandaan while the sample size of 64 people was determined by Purposive Simple sampling technique.The data analysis was conducted using chi square test. The results of the data analysis using chi square test was statistically significant with p value = 0.003 (p<0.005) which showed a relationship between blood pressure and sleep quality. Irregular sleeping pattern leads to physiological changes and imbalance of homeostasis. The active sympathetic nervous system tends to increase peripheral resistance and cardiac output which results unraised blood pressure.